AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN KELOR (Moringa oleifera L.) DAN PENGEMBANGANNYA MENJADI BENTUK SEDIAAN GEL - Asisi, Nur; Uliyah, Uliyah; Amaliyah, Nurul Fitrah; Hasrawati, A (Jurnal Ilmiah As-Syifaa, 2021)
Antioxidants are used to prevent the oxidation of free radical compounds which have a bad impact on the body, including the skin.  One source of antioxidants derived from natural ingredients is Moringa leaves.  Moringa leaves have a number of benefits due to the many active chemical compounds.  The antioxidant activity of Moringa leaves can be optimized by developing Moringa leaves into a gel dosage form.  A literature review regarding the compound content and activity of Moringa leaves was carried out to obtain scientific data that can be used in the development of Moringa leaves as an antioxidant.  Narrative review with data sources from Science Direct, Pubmed, CiterSeerX, and Google Scholars. The Inclusion and exclusion criteria were set to obtain literature according to the scope of the study.  The results of the literature review showed that Moringa leaves contain the main active compounds of polyphenols and flavonoids which have strong antioxidant activity.  Gel dosage form is one of the best choices to optimize the antioxidant activity of Moringa leaves.  HPMC, carbopol and xanthan gum are gelling agent was produced a gel preparation with good pharmaceutical characteristics.